2014
DOI: 10.1021/ie503335h
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Cracking of Supercritical n-Dodecane over Wall-Coated Nano-Ag/HZSM-5 Zeolites

Abstract: A series of Ag modified zeolites were prepared by incipient impregnation of nano-HZSM-5 with AgNO 3 (0.5−2.0 wt %) aqueous solutions. It was found that the ion-exchange and impregnation effect both existed in this impregnation process, resulting in the formation of various silver species which altered the zeolite acid properties. The wall-coated nano-Ag/HZSM-5 zeolites were prepared on the inner surface of 304 stainless steel tubes though the washcoating method. Catalytic cracking of supercritical n-dodecane (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Although the amount of acid sites is smallest than the others, ZSM-5-140 exhibits the highest activity (average conversion of 26.8%) and good stability (r d of 40.9%) among four ZSM-5 zeolites. Qu et al 33 detailedly studied the effects of Si/Al ratio of ZSM-5 zeolites on catalytic cracking of n-dodecane and found that catalytic cracking activities and stabilities increased with the Si/Al ratio of zeolites, and one with the highest Si/Al ratio gave the highest activity and stability. Authors explained that the main reason for it is weakened deactivation effect from coke in the reaction because of the low amount of acid sites.…”
Section: Pyridine-adsorbed Ft-irmentioning
confidence: 99%
“…Although the amount of acid sites is smallest than the others, ZSM-5-140 exhibits the highest activity (average conversion of 26.8%) and good stability (r d of 40.9%) among four ZSM-5 zeolites. Qu et al 33 detailedly studied the effects of Si/Al ratio of ZSM-5 zeolites on catalytic cracking of n-dodecane and found that catalytic cracking activities and stabilities increased with the Si/Al ratio of zeolites, and one with the highest Si/Al ratio gave the highest activity and stability. Authors explained that the main reason for it is weakened deactivation effect from coke in the reaction because of the low amount of acid sites.…”
Section: Pyridine-adsorbed Ft-irmentioning
confidence: 99%
“…There has been a significant effort to find effective catalysts for endothermic reforming, , with most work focused on acid-catalyzed cracking of hydrocarbons using zeolites. Results are zeolite dependent but medium-pore zeolites (e.g., H-ZSM-5) have been shown to be active and stable at the required temperatures and pressures. , Although monomolecular cracking of an alkane to produce olefins is also strongly endothermic, hydrocarbon cracking at high pressures is dominated by bimolecular processes in which hydride-transfer reactions saturate olefins and form smaller alkanes . Work described in a previous paper from some of us showed that olefin production is minimal in acid-catalyzed cracking at high pressures, so that these reaction are nearly thermoneutral and therefore not helpful.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HMP-49 possessed more weak and strong acid sites during TEAOH postsynthesis, demonstrating the enhancement of accessibility of acid sites. After impregnation of Ni particles, on one hand, the new acid sites were probably originated by Ni species with weak acidity; on the other hand, the desorption temperature of strong acid sites has been shifted toward higher temperatures, which may be ascribed to the interaction between Ni particles and zeolitic supports, , compared to parent zeolites. However, whole acid amounts decreased because of the coverage of acid sites by Ni species.…”
Section: Resultsmentioning
confidence: 99%